SYNTHESIS AND CHARACTERIZATION OF NICKEL HYDROXIDE FROM EXTRACTION SOLUTION OF SPENT CATALYST - Kevin Cleary Wanta; Felisha Hapsari Tanujaya; Federick Dwi Putra; Ratna Frida Susanti; Gelar Panji Gemilar; Widi Astuti; Himawan Tri Bayu Murti Petrus (National Research and Innovation Agency (BRIN), 2020)
Nickel is an essential metal element and is applied in various sectors. One of the useful nickel–based derivatives products is nickel hydroxide [Ni(OH)2]. This compound is widely applied as raw material for electrodes of rechargeable batteries, capacitors, electrolyzers, and catalysts. This study focuses on the synthesis of Ni(OH)2 using the hydroxide precipitation method. A solution from the extraction process of spent catalysts was used as a precursor solution. After the precursor solution was obtained, the precipitation process was carried out at pH 10, where the operating temperature was varied at 30–60oC. NaOH, KOH, and MgO solutions were used as precipitating agents. The experimental results show that the Ni(OH)2 compounds were produced optimally at low temperatures, 30oC. It could be indicated from the lowest concentration of Ni2+ ions in the liquid phase that reached that temperature. The three precipitation agents also gave good results in the precipitation of Ni2+ ions, where almost all of the Ni2+ ions were precipitated from the liquid phase. The precipitated products were characterized using SEM, XRD, and XRF. The analysis results showed that the product was agglomerated and formless. The purity of the precipitates formed were 24.1 and 29% for the precipitating agents MgO and NaOH, respectively.